When are Agents Negligible? - Wolfgang Pesendorfer; David Levine (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
We examine the following paradox: In a dynamic setting, an arbitrarily large finite number of agents adn a continuum of agents can lead to radically different equilibrium outcomes. We show that in a simple strategic setting this paradox is a general phenomenon. We also show that the paradox disappears when there is noisy observation of the players' actions: The aggregate level of noise must disappear as the number of players increases, but not too rapidly. We give several economic examples in which this paradox has recently received attention: the durable goods monopoly, corporate takeovers, and time consistency of optimal governmetn policy.
Keywords: 330